Adipocytes promote interleukin-18 binding to its receptors during abdominal aortic aneurysm formation in mice. (10th December 2019) - Liu, Cong-Lin; Ren, Jingyuan; Wang, Yunzhe; Zhang, Xian; Sukhova, Galina K; Liao, Mengyang; Santos, Marcela; Luo, Songyuan; Yang, Dafeng; Xia, Mingcan; Inouye, Karen; Hotamisligil, Gökhan S; et al.
Abstract: Aims: Obesity is a risk factor of abdominal aortic aneurysm (AAA). Inflammatory cytokine interleukin-18 (IL18) has two receptors: IL18 receptor (IL18r) and Na-Cl co-transporter (NCC). In human and mouse AAA lesions, IL18 colocalizes to its receptors at regions rich in adipocytes, suggesting a role of adipocytes in promoting IL18 actions in AAA development. Methods and results: We localized both IL18r and NCC in human and mouse AAA lesions. Murine AAA development required both receptors. In mouse AAA lesions, IL18 binding to these receptors increased at regions enriched in adipocytes or adjacent to perivascular adipose tissue. 3T3-L1 adipocytes enhanced IL18 binding to macrophages, aortic smooth muscle cells (SMCs), and endothelial cells by inducing the expression of both IL18 receptors on these cells. Adipocytes also enhanced IL18r and IL18 expression from T cells and macrophages, AAA-pertinent protease expression from macrophages, and SMC apoptosis. Perivascular implantation of adipose tissue from either diet-induced obese mice or lean mice but not that from leptin-deficient ob/ob mice exacerbated AAA development in recipient mice. Further experiments established an essential role of adipocyte leptin and fatty acid-binding protein 4 (FABP4) in promoting IL18 binding to macrophages and possibly other inflammatory and vascular cells by inducing their expression of IL18, IL18r, and NCC. Conclusion: Interleukin-18 uses both IL18r and NCC to promote AAA formation. Lesion adipocyte and perivascular adipose tissue contribute to AAA pathogenesis by releasing leptin and FABP4 that induce IL18, IL18r, and NCC expression and promote IL18 actions.